Evaluation of a new geriatric foot versus the Solid Ankle Cushion Heel foot for low-activity amputees. (April 2015) - Bonnet, Xavier; Adde, Jean N; Blanchard, François; Gedouin-Toquet, Annick; Eveno, Dominique
Background: It is always a challenge to rehabilitate geriatric amputees to perform self-care skills at home with limited ambulation. A new geriatric foot (with a lower effective foot length) has been specifically designed to reduce residual limb stress and to ease the step completion. Objectives: The aim of this study is to evaluate the benefit of a new geriatric foot versus a Solid Ankle Cushion Heel foot for low-activity persons with transtibial amputation. Study design: Crossover study. Methods: A total of 12 patients were included in this study. Outcome measures: 2-min walking test, Quebec User Evaluation of Satisfaction with Assistive Technology 2.0 questionnaire and pressure socket measurements. Results: The geriatric foot allows for greater patient satisfaction. The maximal pressure was significantly lower in the proximal anterior stump area. No statistical differences were obtained from the 2-min walking test. Conclusion: A geriatric foot designed with a low effective foot length improves the satisfaction and reduces proximal anterior socket pressures for poor-performing persons with transtibial amputation. Clinical relevance: The development and evaluation of feet specifically designed for geriatric persons with transtibial amputation could improve their specific requirements and satisfaction.